Cooperativity of Mus81.Mms4 with Rad54 in the resolution of recombination and replication intermediates - Matulova, Petra; Marini, Victoria; Burgess, Rebecca C; Sisakova, Alexandra; Kwon, Youngho; Rothstein, Rodney; Sung, Patrick; Krejci, Lumir (The Journal of biological chemistry, 2009)
The Saccharomyces cerevisiae Mus81.Mms4 protein complex, a DNA structure-specific endonuclease, helps preserve genomic integrity by resolving pathological DNA structures that arise from damaged or aborted replication forks and may also play a role in the resolution of DNA intermediates arising through homologous recombination. Previous yeast two-hybrid studies have found an interaction of the Mus81 protein with Rad54, a Swi2/Snf2-like factor that serves multiple roles in homologous recombination processes. However, the functional significance of this novel interaction remains unknown. Here, using highly purified S. cerevisiae proteins, we show that Rad54 strongly stimulates the Mus81.Mms4 nuclease activity on a broad range of DNA substrates. This nuclease enhancement does not require ATP binding nor its hydrolysis by Rad54. We present evidence that Rad54 acts by targeting the Mus81.Mms4 complex to its DNA substrates. In addition, we demonstrate that the Rad54-mediated enhancement of the Mus81.Mms4 (Eme1) nuclease function is evolutionarily conserved. We propose that Mus81.Mms4 together with Rad54 efficiently process perturbed replication forks to promote recovery and may constitute an alternative mechanism to the resolution/dissolution of the recombination intermediates by Sgs1.Top3. These findings provide functional insights into the biological importance of the higher order complex of Mus81.Mms4 or its orthologue with Rad54.
Keywords: DNA vazebné proteiny; DNA Replication; nestabilita genomu; DNA-helikasy; DNA Helicases; helikasy RecQ; Endonucleases; replikace DNA; rekombinace genetická; Flap Endonucleases; endonukleasy; Saccharomyces cerevisiae Proteins; genom fungální; Transcription Factors; DNA Repair Enzymes; enzymy opravy DNA; RecQ Helicases; DNA-Binding Proteins; transkripční faktory; Recombination, Genetic; DNA, Fungal; Genomic Instability; trans-aktivátory; DNA fungální; Trans-Activators; "flap" endonukleasy; Saccharomyces cerevisiae; multienzymové komplexy; Adenosine Triphosphatases; Multienzyme Complexes; Saccharomyces cerevisiae - proteiny; adenosintrifosfatasy; Genome, Fungal